Creativity and passion through clay / Mahizan Hijaz Mohammad - Mohammad, Mahizan Hijaz (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
One hundred and fifty students from three Maktab Rendah Sains MARA (MRSM) branches; Kuala Klawang, Sungai Besar and Parit had participated in the Ceramic Fest 2019. It was a collaborative programme between the Faculty of Art and Design (FSSR), UiTM Perak Branch and Maktab Rendah Sains MARA (MRSM). The programme was held from April 26 - 28, 2019.